A taxonomic revision of Notothlaspi (Brassicaceae), a specialist alpine genus from New Zealand - Heenan, Peter B. (Phytotaxa, 2019)
The New Zealand endemic alpine genus Notothlaspi comprises three species from the South Island mountains. Notothlaspi australe and the newly described N. viretum occur on rock bluffs and outcrops and their associated stony soils. Notothlaspi australe occurs in Nelson, Marlborough and north Westland, northern South Island, and N. viretum is endemic to the highest peaks of Red Hills, Marlborough, where it occurs on ultramafic soils. Notothlaspi viretum is segregated from the sympatric N. australe by its numerous, closely placed rosettes that form compact cushions and the leaves are linear to linear-narrowly lanceolate. These two species are distinguished from the scree-specialist, rosette forming, monocarpic N. rosulatum by their perennial growth habit, forming cushions with branched stems, narrower leaves, axillary and solitary flowers, and smaller silicles. Notothlaspi rosulatum is known from Nelson, Westland, Marlborough, Canterbury and Otago. Notothlaspi rosulatum var. hursthousei and N. notabilis are treated as synonyms of N. rosulatum, and N. australe var. stellatum is placed as a synonym of N. australe. All names are typified and a key is provided.